A path model of psychosocial constructs predicting future Zika vaccine uptake intent. Issue 36 (23rd August 2019) - Guidry, Jeanine P.D.; Carlyle, Kellie E.; Perrin, Paul B.; LaRose, Jessica G.; Ryan, Mark; Messner, Marcus
Abstract: Objective: The recent Zika virus outbreak, while no longer an international public health emergency, is still a serious threat, particularly to pregnant women and babies born to pregnant women infected with the virus. This study examined the predictive effects of psychosocial constructs on self-reported intent to get a future Zika vaccine among women of reproductive age. Methods: Data were collected using an online survey with a representative sample of 339 women ages 18–49 from the continental United States. The survey addressed variables originating with the Extended Parallel Processing Model (EPPM) as related to future Zika vaccine uptake intent. Results: Three quarters of all respondents reported intention to get a future Zika vaccine. Path modeling revealed a direct effect of perceived susceptibility, self-efficacy, and response efficacy on future Zika vaccine uptake intent, as well as an indirect effect of perceived susceptibility through both self-efficacy and response efficacy. In addition, the final model showed an indirect effect of perceived severity on Zika vaccine uptake intent through self-efficacy and response efficacy and accounted for 54.6% of the variance in vaccination intent. Conclusions: These findings have implications for future Zika vaccine promotion campaigns. This study confirms the importance of perceived susceptibility, self-efficacy, and response efficacy for use in Zika vaccine uptake campaigns; in addition, when using perceived severity, both self-efficacy and response efficacy should be considered in message design.